Sitios da morte sem fim: espaço de focalização em Pedro Páramo. - Oliveira, Jefferson Cardoso (2013)
This dissertation examines some elements of the complex spatiality in Pedro Páramo, verifying how these elements stablishes associations to the focus and structure of the only novel written by the Mexican writer Juan Rulfo. Our research is based on the correlation between space and focus and how the space is related to the structure of the text. We take into consideration the critical aproaches presented by Luis A. Brandão, Ozíris B. Filho among others who have studies based on topoanalysis. The story is told from the perspective of multiple narrators who have died, changing the settings of time and space that rules the novel, making it very atypical. These characteristics are strongly linked to the peculiar structure of the narrative and the behavior of the characters and narrators who offers a post mortem angle of their stories. Due to the breaking of barriers separating life and death, the characters move through several layers of time and space, doomed to pay his penalties indefinitely on Comala, the ghost town where the story is set.